Investigation on heat transfer and flow-induced vibration of three cylinders in equilateral triangle arrangement. (July 2022) - Zou, Qunfeng; Ding, Lin; He, Haoyu; Song, Tian
Abstract: Flow-induced vibration (FIV) and heat transfer of three circular cylinders were numerically investigated in the reduced velocity range of 3 ≤ U ⁎ ≤ 15. To obtain the vibration and heat transfer characters, the influence of FIV and Richardson number (0 ≤ Ri ≤ 1) on the heat transfer performance are studied. It's found that the rise of Ri can lead to the suppression of FIV and narrow the reduced velocity ( U ⁎ ) range of lock-in. The amplitude and lift coefficient of two downstream cylinders are higher than that of 1st cylinder (upstream one) for most of U ⁎ . The FIV can significantly enhance the heat transfer of 2nd and 3rd cylinders (downstream cylinders), the highest increments of averaged Nusselt number are 9.74% (2nd cylinder) and 9.78% (3rd cylinder), which can be obtained when Ri = 0.5 and U ⁎ = 5. Meanwhile, the distribution of local Nusselt number shows that the heat transfer mainly occurs at the upstream side of each oscillator. The heat transfer characteristics on the surface of each cylinder are closely influenced by the thickness of thermal boundary, which determines the gradient of temperature around cylinders.